El holismo cosmoteándrico de Raimon Panikkar y el holismo sustancial de Fernando Inciarte: ¿dos metafísicas de sistema? - Espinosa, Zaida (2020)
“Ramon Panikkar’s Cosmotheandric Holism and Fernando Inciarte’s Substantial Holism: Two Metaphysics of System?”. The aim of this article is to compare the metaphysics of Raimon Panikkar and Fernando Inciarte. When examining, in the first two parts, the way in which both answer to the main metaphysical question of what it is, we find the apparently opposed approaches of a metaphysics of substance (Inciarte) and a metaphysics of the system based on the cosmotheandric intuition, which has relations as the fundamental category (Panikkar). In the third part, we compare both approaches in order to assess the role that the notion of system plays in them so as to determine, in the end, that the metaphysics of substance is more related to the metaphysics of the system than it may appear at first.